Character Education through Islamic Values: A Study of the 'One Mosque Memorizers' Program at Pondok Wadil Qur'an Tangerang - Suryanti (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2023)
Purpose – This study aims to examine the implementation of character education through the 'One Mosque Memorizers of the Qur’an' program at Pondok Wadil Qur’an Tangerang, focusing on integrating Islamic values of tolerance, honesty, and humility into the educational framework. Design/Methods/Approach – A qualitative approach was adopted, comprising structured interviews and focus group discussions with students, educators, and administrators. Thematic analysis was employed to identify patterns in the integration of Islamic values in character education and their impact. The study emphasized reliability and validity through triangulation and member checking. Findings – The program effectively imparts Islamic values as foundational elements of character education. Tolerance is highlighted through the acceptance of religious diversity, honesty is fostered through truthful practices, and humility is encouraged through respectful behavior. The study demonstrates the positive impact of these values on students' moral and ethical development. Research Implications/Limitations – This research contributes to the understanding of character education in non-formal Islamic educational settings. However, its focus on a single program and reliance on qualitative data limit its generalizability and may introduce subjective interpretations. Practical Implications – The findings have significant implications for educational institutions, policymakers, and religious leaders, offering insights into the integration of religious values into educational practices. This approach addresses moral and ethical challenges, shaping a more ethical and harmonious society. Originality/Value – This study presents a unique perspective on character education, emphasizing the role of Islamic values in shaping individual character and societal ethics. It provides a model for incorporating religious values into educational systems, contributing to the development of morally upright and socially responsible individuals.